Comparison of Online Gambling Legal Regulations Between Indonesia and The United States - Darmawan, Nino Gilang; Tumanggor, MS; Hakim, Lukman (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
Gambling in Indonesia has historically been a social ill strictly prohibited by various regulations, such as Article 303 of the Criminal Code, Law No. 7 of 1974, and the Electronic Information and Transactions (ITE) Law. However, a legal dualism currently exists , where gambling is prohibited for moral and religious reasons, while a legal loophole exists through the terms